2016
DOI: 10.1161/circgenetics.116.001402
|View full text |Cite
|
Sign up to set email alerts
|

SCARB1 Gene Variants Are Associated With the Phenotype of Combined High High-Density Lipoprotein Cholesterol and High Lipoprotein (a)

Abstract: Lp(a) is a proatherogenic lipoprotein particle containing one mole of apolipoprotein(a) (apo(a)) and a mole of LDL. 15,16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…For example, SR-BI mostly leads to the selective uptake of neutral lipids, such as cholesteryl esters from the Lp(a) core, but may not significantly alter the plasma clearance of apo(a) (23). The physiologic relevance of these observations on the interaction of Lp(a) with SR-BI in humans is not clear, but patients with heterozygous loss of function mutations in SR-BI show increased plasma levels of Lp(a) (24). LRP1 may contribute to Lp(a) clearance via its affinity for apoB or Lp(a) and the different affinities for apoE isoforms.…”
Section: Specific Research Priorities and Recommendationsmentioning
confidence: 99%
“…For example, SR-BI mostly leads to the selective uptake of neutral lipids, such as cholesteryl esters from the Lp(a) core, but may not significantly alter the plasma clearance of apo(a) (23). The physiologic relevance of these observations on the interaction of Lp(a) with SR-BI in humans is not clear, but patients with heterozygous loss of function mutations in SR-BI show increased plasma levels of Lp(a) (24). LRP1 may contribute to Lp(a) clearance via its affinity for apoB or Lp(a) and the different affinities for apoE isoforms.…”
Section: Specific Research Priorities and Recommendationsmentioning
confidence: 99%
“…Human SCARB1 gene variants have been shown to be associated with abnormal lipids in women with coronary artery disease (132), and analysis of common genetic variations near the SCARB1 locus shows significant association with plasma HDL-C levels (133), as well as with combined high HDL-C and high lipoprotein (a) (134). Intestinal SR-B1 is upregulated in the insulin-resistant state and is associated with overproduction of intestinal apoB48-containing lipoproteins (135).…”
Section: Sr-b1 Function In Other Pathophysiological Conditionsmentioning
confidence: 99%
“…However, the observation that their platelets have increased cholesterol content and are prothrombotic[14] suggests that their HDL has less cholesterol efflux capacity. As in mice, recent studies have demonstrated that human carriers of loss of function SCARBI variants have increased plasma Lp(a) suggesting that hepatic SR-BI also mediates clearance of proatherogenic Lp(a) in humans[34]. However, future studies need to address whether hepatic SR-BI also contributes to the clearance of atherogenic remnant lipoproteins in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the in vivo clearance of Lp(a) was decreased in SR-BI deficient mice and overexpression of hepatic SR-BI markedly increased the clearance of Lp(a)[33]. Importantly, studies showed that human carriers of 6 different SCARB1 gene variants had increased plasma levels of Lp(a), and the variants had reduced ability to mediate the uptake of Lp(a) CE[34]. …”
Section: Effects Of Hepatic Sr-bi On Atherosclerosis and Plasma Lipopmentioning
confidence: 99%